Uso de suplementos alimentares entre atletas : prevalência, perfil e fatores associados - Nabuco, Hellen Clair Garcez (2015)
The prevalence of consumption of dietary supplements among athletes has been studied extensively, with studies with elite athletes and college. However, few data on Brazilian athletes are available, particularly studies approaching the factors associated with the practice of supplementation. Objective: Investigate the profile, prevalence and factors associated with use of dietary supplements among Brazilian athletes. Methods: It is a crosssectional study of 182 athletes of both genders. The athletes answered a questionnaire containing sociodemographic and sports information, current consumption of supplements, use of pharmacological substances, and also about body image disorder (BSQ) and muscle dysmorphia (MASS). Results: Forty-seven percent were athletes consuming at least one type of supplement. The most consumed supplement is whey protein (53.5%). Main reason given for the use of supplements was to improve performance (70.9%). The main source of information was the coach (36%). Regarding the use of pharmacological substances, 18% of athletes reported using, and anabolic steroids were the most cited (51.5%). Most of the users of these substances also used supplements (87.5%). According to the bivariate analysis, male, aged 25 to 29 years, having a paid activity, consumption of pharmacological substances, body image disturbance, risk of muscle dysmorphia, power modality and absence of medical care were factors associated with consumption supplements. After the regression analysis, the consumption of supplements was related to male consumption of pharmacological substances and risk of muscle dysmorphia. Conclusion: Almost half of the sample was using food supplements and many athletes used more than 3 types of supplements concurrently. The vast majority of users of pharmacological substances were users of supplements. Male athletes, with risk of muscle and make use of pharmacological substances dysmorphia are factors that are associated with the consumption of supplements. The results of this present study indicate the necessity of nutrition education along with the coaches and trainers because of the great influence of these professionals in choosing these products